STUDY ON THE EFFECT OF COMPOSITION AND VARIATION OF Sn/Zn COOLING MEDIA ON NICKEL ALLOY STEEL THROUGH HOT FORGING AND AUSTEMPERING - Satrio Herbirowo; Martin Harimurti; Septian Adi Chandra; Dedi Pria Utama; Faried Miftahur Ridlo; Yeni Muriani Zulaida; Bintang Adjiantoro (Jurnal Sains Materi Indonesia, 2021)
STUDY ON THE EFFECT OF COMPOSITION AND VARIATION OF Sn/Zn COOLING MEDIA ON NICKEL ALLOY STEEL THROUGH HOT FORGING AND AUSTEMPERING. Laterite steel with nickel content is expected to be a solution to overcome the lack of domestic steel availability and dependence on imports. This research was conducted to develop Nickel-Chromium-Molybdenum alloy steel used Grinding ball for cement industrial applications. Grinding ball is the one of imported steel products needed to be crushing and size reduction the ores or cement. In addition to import issues, grinding balls have a significant problem: their mechanical properties that do not meet SNI 1049 require the material to have a minimum hardness value of 45 HRC. In this study, the characteristics of Nickel alloy steel were investigated further through heat treatment of forgings heated at the austenitizing temperature of 950 °C and austempering with variations in the cooling medium of Sn/Zn solution. The cooling medium was chosen because it has a melting temperature in the phase diagram area to form the bainite microstructure with complex and challenging characteristics, both of which are required in material for grinding ball applications. In particular, the hardness value that passed the SNI 1069 standard was the use of samples with a Cr-Mo alloy of 1%-wt with a hardness value of 45.92 HRC for Sn Austemper and 48.07 HRC for Zn austemper.